David the Invincible: Philosophy as a Lifestyle - Petrosyan, Silva (Տիգրան Մեծ)
The most outstanding representative of the history of Armenian philosophy, Neoplatonic think-er of the V-VI centuries, David the Invincible continues the tradition reached the peak of its development in the Ancient Greece by Socrates and Plato, according to which philosophy is first of all a way of life, a means of transformation and perfection of the human being. Following the principles of the Greek Paideia David considers philosophy as a care of the soul, in which theory and practice are intertwined, and cognition of the world depends on the efforts of self-improvement by a subject. Author shows that in David’s definitions of philosophy is clearly seen the significance of self-formation, “zardarum” in the process of reality formation, comprehension or rethinking. It is also mentioned that we can use Michel Foucault’s notion of the “care of the soul” and Pierre Hadot’s notion of “spiritual practices’’ to characterize David’s optimistic philosophy, which was developed further in the theories of Armenian thinkers Grigor Narekatsi, Grigor Magistros, Hovhannes Imasta-ser, Arakel Sjunetsi, etc.
Keywords: History of philosophy